Sensory Processing Abilities in Elementary Students with Suicide Ideation: A Preliminary Study on the Clinical Effects of School Sandplay Group Counseling - Kim, Dong-Jun; Kim, Soo-Jeong; Ahn, Un-Kyoung (School Counselling and Sandplay, 2023)
Lowenfeld developed sandplay therapy as a technique that allows children's multidimensional thoughts and emotions to be expressed more freely, while at the same time combining not only visual but also tactile and sensory factors. Since then, sandplay therapy has been used as a psychotherapy technique in various clinical settings around the world, but there has been no evidence-based research on sandplay therapy and sensory processing ability. This study investigated the clinical effects of school sandplay group counseling on sensory processing abilities in 20 sixth-grade elementary school students with suicide ideation. School sandplay group counseling was conducted for 8 sessions in 12 weeks, from March 2023, to June 2023. The subjects were sixth-grade students with suicide ideation from an elementary school in Chungcheongbuk-do, South Korea, with a single group of 10 males (50%) and 10 females (50%) without a control group. The average age of the participants was 11.74, with a range of 11.25-12.15. The Korean version of the SIQ-JR and the Korean version of the AASP were used as pretest and posttest instruments. The data were analyzed using SPSS 29.0. the paired-sample t-tests indicated statistically significant changes in low registration (p = .025), and suicide ideation (p = 0.017). The results of this study suggest that school sandplay group counseling may have clinical effects on sensory processing abilities and suicide ideation in elementary school children with suicide ideation. KCI Citation Count: 0